Study on computational efficiency of composite schemes for convection-diffusion equations using single-grid and multigrid methods - Jingfa LI; Bo YU; Yi WANG; Yawen TANG; Huijie WANG (Journal of Thermal Science and Technology, 2015)
The computational efficiency of different composite schemes for the convection terms of the convection-diffusion equations is systematically studied in this paper. They are evaluated by the problems of lid-driven flow and natural convection in a square cavity, within the framework of single-grid and multigrid finite volume methods on collocated grids. For the convection schemes, the computational efficiencies of QUICK scheme and commonly used ten composite schemes (SMART, STOIC, MINMOD, etc.) are compared under the same calculation conditions. The influences of implementation strategy of composite schemes, grid number, Reynolds number and Rayleigh number on the computational efficiency are analyzed. It is found that the computational efficiency of composite schemes is close to that of QUICK scheme without extra calculation burden.